Visiting Fellow Programme at Universitas Airlangga Surabaya, Indonesia - UiTM, Faculty of Law (Faculty of Law, 2019)
Under the Beyond Boundaries Law Programme, two of our lecturers, Puan Habibah Omar and Dr. Noraiza Abdul Rahman visited Universitas Airlangga (UNAIR) upon being appointed as Visiting Fellows of the University. The visit was made from 28 April-3 May 2019. They joined another fellow lecturer, Cik Mazlifah Mansoor who has been at Universitas Airlangga since 22 April 2019 on the same fellowship programme. These visits have provided excellent platform for academicians from both universities to discuss, share and strengthen mutual relation and at the same time discussing ventures for future collaboration. Puan Habibah gave public lectures to both undergraduate and postgraduate students in the area of Administrative Law and matters relating to government's accountability. Dr. Noraiza on the other hand, gave a lecture on research and legal methodology to the first and second year students of Universitas Airlangga.